Sperm viability and quantity of mud crab, Scylla tranquebarica in different cryoprotectants - Chen, Cheng Ann; Siti Nur Fatihah; Sylvester C. Simon; Hasrul H. Hashim; Harman Muhd-Farouk (BIOFLUX SRL, 2018)
The aim of the present study was to determine the optimum concentrations of differentcryoprotectants and to determine the sperm quantity with different durations of exposure for S.tranquebarica’s sperm. The body weight of S. tranquebarica was 280-350 g. In the present study, maleS. tranquebarica were dissected out and got the sperm to determine its viability and quantity using sixtypes of cryprotectants (glycerol, glycine, methanol, dimenthyl sulfoxide (DMSO), ethylene glycol (EG)and proline). The sperm was exposed with different durations of 5, 15, 30 and 60 min at roomtemperature (25oC). For the cryoprotectant glycine 10%, there was the highest mean sperm viabilitywith 84.75±1.01% (exposure at 60 min). Meanwhile, 15% proline was the lowest mean sperm viabilitywith 15.39±0.39% after exposure for 60 min at room temperature. There were significant differences between the duration of exposure for some types of cryoprotectants (p-value < 0.05). As a conclusion, 10% glycine was the best cryoprotectant of mud crab, S. tranquebarica. As a recommendation, S. tranquebarica’s sperm should be preserved in the cold conditions such as -20oC, -80oC and -196oC (liquid nitrogen) to determine the sperm viability and quantity for further breeding programs and biochemicalchanges